Penerapan Simple Additive Weighting Pada Sistem Otomatisasi Surat Teguran SAMSAT Mataram Melalui SMS Gateway - Muhammad Reza Syachrani; Nisa Hanum Harani; M Harry K Saputra (STMIK Budi Darma, 2021)
Remind or notify the Taxpayer of unnecessary obligations so that a Reprimand letter arises. Choosing a Reprimand letter and sending a Reprimand letter is not effective because it takes a lot of time and money. Therefore, to be able to overcome the existing problems, it is necessary to automate the selection of Reprimand letters using the Simple Additive Weighting (SAW) method which is a multi-criteria decision support method. As well as sending automatic Reprimand letters using Short Message Service (SMS) using the Gammu library. So that it can make it easier for users to choose and send letters so that it can be done faster and at lower costs. The results of the tests carried out in terms of time, SAW has a faster time with conventional systems by only taking 8,620 seconds. Furthermore, testing is carried out in terms of the cost of the SMS gateway, which is more affordable than the conventional system that was previously applied with a cost difference of 99.7%